Alat Penyeleksi Kelayakan Udang Ekspor Berdasarkan Suhu Berbasis Arduino Uno - Mhd Ridho Wiratama; Ade Zulkarnain Hasibuan; Arnes Sembiring (UIN Sumatera Utara, 2022)
The development of the use of technology in the industrial world is growing rapidly, it makes conventional tools and machines begin to be abandoned and then switch to more modern tools and machines with automatic control, thus helping the workforce to work more optimally. Selection of goods is an activity that is mostly carried out in the industrial world in the process of export and import activities, such as grouping by temperature. Previously some of the shrimp selection was done manually, this process is very inefficient because it requires a lot of time and effort. The ATmega32 microcontroller (Arduino Uno) functions as the control center of the system, infrared temperature sensor with the MLX90614 series which functions to detect the temperature scale, DC motor as a conveyor drive, IR sensor detects shrimp objects that pass and makes the computer stop then the temperature sensor will detect the temperature of the shrimp object and displays the temperature value on the 20x4 LCD. The servo motor as a sorter forms a partition or gate indicating which direction the shrimp object will be positioned. Through the stages of the mechanical design process and system programming using the Arduino IDE program, as well as the results of testing and data analysis, a system that can work well and continuously is obtained. Although the system is designed only in the form of a prototype, but by using equipment with industrial standards it can be applied to support automated and efficient work in the industrial sector.Keywords: Shrimp, Export, Microcontroller, Arduino Uno, MLX90614, Motor DC.